GENDER AND SELF-REGULATED WRITING AMONG INDONESIAN HIGH SCHOOL STUDENTS - Salsabila Saifa Fitra Ichwany; Ekaning Dewanti Laksmi; Evi Eliyanah (Universitas Darussalam Gontor, 2026)
This study investigates Indonesian senior high school students’ self-regulated writing (SRW) strategies in composing analytical text. In particular, the study examines gender differences in the use of SRW strategies. While prior research on SRW has explored SRW strategies across various contexts, limited studies have examined their use among high school learners across gender and within specific genres, resulting in an incomplete understanding of how these strategies are performed by students of different gender and in context-specific writing tasks. This study employed a quantitative descriptive design, involving 110 eleventh-grade students from a reputable public high school in Malang, Indonesia. Data were collected using the Writing Strategies for Self-Regulated Learning Questionnaire (WSSRLQ) and analyzed through descriptive statistics and independent sample t-test. The findings revealed that students demonstrated a high level of SRW strategy use (M = 3.23), with social-behavioral strategies emerging as the most often utilized (M = 3.38), while metacognitive strategies were the least employed (M = 3.19). Although female students reported slightly higher use of SRW strategies (M = 3.31) than males (M = 3.26), no statistically significant gender difference was found (p > 0.05). These findings suggest that SRW strategy use is shaped more by contextual learning conditions than by gender. Pedagogically, the study highlights the importance of integrating explicit metacognitive strategy instruction alongside collaborative learning practices to enhance students’ writing development, particularly in demanding genres such as analytical exposition text.